Knowledge Management and Human Resource Management to Innovate: An Empirical Analysis in the Textile Industry - Martínez-Arroyo, Jaime Apolinar; Peñaloza Talavera , María Francisca; Valenzo Jiménez, Marco Alberto; Madrigal Moreno, Flor (Mercados y Negocios, 2024)
This research aims to understand the impact of knowledge management and human resource management on innovation in textile industry companies in central-western Mexico. This is a qualitative, descriptive, correlational study with a non-experimental, cross-sectional design. The sample is simply random and is made up of 386 companies in the textile industry. A structured questionnaire was applied using a Likert-type scale with five ranges. The information analysis used the Structural Equation Model (SEMPLS). In the results, the analysis of the statistical parameters t – t-student and p-value confirm the statistical significance of the Path coefficients with 95% confidence. The results of the research coincide with some of the literature. This research fills a gap in the literature on the phenomenon studied.